2011
DOI: 10.1038/tpj.2011.51
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetic predictors for EGFR-inhibitor-associated skin toxicity

Abstract: The aim of this study was to investigate pharmacogenetic determinants of skin rash associated with epidermal growth factor receptor (EGFR) inhibitor treatment. A total of 109 prospectively sampled cancer patients, receiving the first treatment with an EGFR inhibitor, were genotyped for functional EGFR polymorphisms and tagging variants in genes involved in receptor downstream signaling. Skin rash was absent in 26 (23.9%) patients and associated with shorter overall survival compared with patients presenting sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(59 citation statements)
references
References 40 publications
4
54
1
Order By: Relevance
“…A cohort of 211 cancer patients was prospectively included in this study according to a protocol described earlier [39]. There were 77 (36.5 %) female and 134 (63.5 %) male participants with a median age of 69 years (range: 43-87 years).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort of 211 cancer patients was prospectively included in this study according to a protocol described earlier [39]. There were 77 (36.5 %) female and 134 (63.5 %) male participants with a median age of 69 years (range: 43-87 years).…”
Section: Resultsmentioning
confidence: 99%
“…Plasma samples (n = 211) were derived from patients included in the Dermatoxgen study, which is a prospective, multicenter study designed to investigate pharmacogenetic factors of skin toxicity induced by EGFR inhibitors, as already reported in previous publications [18, 19, 39]. The study includes patients with histologically confirmed solid tumors (pancreatic, colon, head and neck or non-small cell lung cancer) who are first-time treated with an EGFRI (erlotinib, gefitinib, cetuximab or panitumumab).…”
Section: Methodsmentioning
confidence: 99%
“…Other groups were not able to confirm this data 36–38. Comparably, EGFR intron‐1 polymorphism was also not identified as a predictor of Cet‐ST or outcome in patients receiving oral tyrosine kinase inhibitors such as erlotinib or gefitinib 40, 41. Reasons for this ambiguity may be the disconcordance of EGFR intron‐1 repeat number between primary tumour and metastases36 or the varying cut‐off definitions 38.…”
Section: Discussionmentioning
confidence: 98%
“…Other studies investigated whether genetic variation within the EGFR gene could predict EGFR inhibitor-associated skin toxicity [83, 84]. Some polymorphisms and haplotypes have been identified but have not been confirmed in larger RCTs.…”
Section: Safetymentioning
confidence: 99%